Positive Ki-67 Expression of Alkaloid Fractionate of Cyperus esculentus on Lead-induced Testicular Toxicity in Male Albino Rat (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The study investigated the positive Ki67 expression of alkaloid fractionates of C.esculentus on the testis of male albino rats. Forty adult male albino rats were grouped into four (4) (n=10). Group 1 was given saline only plus feed and water, and Group 2 was given 30 mg/kg body weight of lead acetate compound plus feed and water; Group 3 was given 50 mg/kg body weight of alkaloid fractionate of C. esculentus and 30 mg/kg body weight of lead plus feed and water and group 4 was given 100 mg/kg body weight of alkaloid fractionate of C. esculentus and 30 mg/kg body weight of lead acetate compound plus feed and water orally. This experiment was conducted for 4 weeks. The sacrifice of experimental animals was taken 24 hours after the experiment, and testes were harvested for histological and immunohistochemistry studies using the H&E and Ki67 immunostain, respectively. Histology and immunohistochemistry of the testes, sperm parameters, sex hormones, and levels of malondialdehyde (MDA), catalase (CAT), glutathione (GSH), and superoxide dismutase (SOD) were the parameters used for the investigation.. According to the results, there was positive expression in Leydig cells and also in an increased series of spermatogenesis of the testes in the rats of groups administered with lead and alkaloid fractionate of Cyperus esculentus different doses 3 and 4 compared to lead acetate control group. A significant increase in the level of hormones suhc as total testosterone (TT), follicle-stimulating hormone (FSH), and luteinizing hormone (LH). levels in groups 3 and 4 (p< 0.05) compared to the lead acetate control group (2) was recorded. MDA levels significantly increased in the treated group(2). In groups treated with lead acetate and alkaloid fractionate of C. esculentus, positive expression was observed in the seminiferous epithelium and in sperm quality. In conclusion, This study demonstrated positive Ki-67 expression of alkaloid fractionate of C. esculentus on testicular lead-induced toxicity in albino rats.
Keywords: Alkaloid; Lead; Testicular toxicity; Spermatogenesis; Ki-67 expression